2017
DOI: 10.1002/rnj.270
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Persian Version of Care Dependency Scale in Nursing Homes

Abstract: The Persian version of the CDS can help clinicians and nurses to assess patients' need and the degree of care dependency among older adults in Persian-speaking areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A higher score indicated more stress. In Iran, validity of the Persian version of this questionnaire has been proved by Rajabi and Naderi through factor analysis, convergent validity has been proved through Beck Depression Inventory and divergent validity has been proved through Rosenberg Self-Esteem Scale (6). Cronbach α coefficient for the whole questionnaire in this study was 0.91.…”
Section: Methodsmentioning
confidence: 54%
“…A higher score indicated more stress. In Iran, validity of the Persian version of this questionnaire has been proved by Rajabi and Naderi through factor analysis, convergent validity has been proved through Beck Depression Inventory and divergent validity has been proved through Rosenberg Self-Esteem Scale (6). Cronbach α coefficient for the whole questionnaire in this study was 0.91.…”
Section: Methodsmentioning
confidence: 54%
“…Although the number of samples in their study was higher than our subjects, correlation in Cronbach's alpha value supports the reliability of our tool. A similar study by Rajabi et al 22 reported a Cronbach's alpha of the whole scale equal to 0.95. Their results supported validity and reliability of the Farsi version of ICF to assess care needs and dependency in senior citizens, which is consistent with the present study.…”
Section: Reliability and Internal Consistency Of The Toolmentioning
confidence: 70%
“…A Frisian version (Dijkstra et al, 2003), investigated in a study with nursing home residents in the northern part of the Netherlands yielded the same factorial structure as the Chinese version for proxy assessment in nursing homes. An Arabic version (Boggatz et al, 2009) that was used in Egypt for both self-assessment by older people and proxy assessments by their non-professional family members showed similar results to those of Piredda et al (2016Piredda et al ( , 2020 and Rajabi et al (2017) with one factor for support of basic needs and one factor for support of psychosocial needs.…”
Section: Backg Rou N Dmentioning
confidence: 75%